Effect of Different Factors on the Short-Term Outcome of Chinese Patients With Primary Chronic Subdural Hematoma at Different Age Groups: A Two-Center Retrospective Study - Huang, Jinhao; Tian, Ye; Song, Yiming; Hu, Rong; Zhang, Shuixian; Gong, Zhitao; Liu, Xuanhui; Luo, Hongliang; Gao, Chuang; Wang, Dong; Feng, Hua; Zhang, Jianning; et al. (Frontiers in Aging Neuroscience, 2019)
Background The incidence of symptomatic chronic subdural hematoma (CSDH) is increasing in Chinese aging population, but its clinical and demographic knowledge is still lacking. This study sought to outline the clinical and demographic data of CSDH patients from two medical centers in Tianjin and Chongqing to provide a better understanding for CSDH treatment in China. Methods Age, sex, etiologies, conscious level on admission, treatment strategies, outcome at discharge, recurrence, and concomitant disease of enrolled patients were recorded. The data were further analyzed after the patients were sub-grouped into young/middle (less than 60 years old) and old (over than 60 years old) age groups. Results A total of 1281 CSDH patients were enrolled. Of these, 85.01% were male and 51.91% were aged between 60 and 80 years. 57.61% patients encountered head trauma before diagnosing CSDH. The top three clinical symptoms at admission were headache (58.55%), dyskinesia (36.92%), and dizziness (33.96%). Headache as well as dizziness often happened in young/middle age group, while dyskinesia often occurred in the old age group. The most common concomitant diseases were cardio-cerebrovascular system diseases (41.14%). The concomitant respiratory diseases in aged patients led to unfavorable outcomes (p = 0.049, OR:0.357). The prognosis of old age subgroup receiving conservative treatment was better than those who received burr-hole drainage treatment (p < 0.015, OR:4.091). Conclusion CSDH mostly occurs in aged and male population with a history a head trauma. The respiratory disease often results in unfavorable outcomes in aged patients. Conservative treatment might benefit some patients.